Challenge of Residence Time Distribution Curve in Tundish for Continuous Casting of Steel. Issue 10 (21st June 2022) - Ding, Changyou; Lei, Hong; Chen, Shifu; Zhang, Han; Zhao, Yan; Zou, Zongshu
Abstract : The residence time distribution (RTD) curve is a simple and useful method to analyze the flow behavior in the tundish. In the last decades, analysis result acquirement based on the RTD curve has been applied to design and optimize the flow control devices in a simple bare tundish or a multistrand tundish. There are many factors to affect the acquirement and analysis of the RTD curve, such as the tracer, the measuring technology, and the analysis model. In order to find a solution for the above issues, the latest progress and research status of RTD curve are discussed in the fields of water model, mathematical model, RTD analysis model, and measuring technology. After comparison, the KCl solution is a good tracer, and its tracer concentration and volume can be determined by the dimensionless tracer parameter ( Dtp ). The extended combined model can be applied to analyze the RTD curve by pulse input of tracer, and the mean residence time is the key parameter to identify the difference in fluid characteristics among the strands. Abstract : A vast volume of literature is extensively reviewed to discuss the tundish residence time distribution curve. Some tips are suggested for the acquisition and processing of the residence time distribution curve in tundish. These tips would provoke tundish metallurgy research activities leading to more reliable results and information for the flow field.